CRITICAL OF THOUGHT MUHAMMAD SYAHRUR (A REFLECTION) - Siti Aisah (Universitas Islam Negeri Mataram, 2019)
This paper aims to examine the thoughts of Muhammad Syahrur which is sourced from his book al-Kitab wa al-Qur'an: Qira’ah Mu'ashirah. Then compared also with the thought of Thahir al-Syawwaf which originates from his book entitled Qira’ah Mu'ashirah Syahrur, which has the title Tahafut al-Qira’ah al-Mu’ashirah. The method used is the study of literature on books from both thinkers. The results showed that the Methodology used by Syahrur in understanding God, nature, and humans is a philosophy with a focus on the philosophy of materialism. Then in understanding the characteristics and power of Islamic law, it must be stated two characteristics of hanafiyyah and istiqomah. These two properties are very contradictory but complementary. These two characteristics then gave birth to the limit theory. With this limut theory, Islamic law will have a dynamic movement in the midst of turmoil and the development of modern reality. Furthermore, what is stated by Syahrur, according to Syawwaf, is inseparable from the method of thinking that uses the philosophy of Marxism. Where social reality is used as a foothold in establishing law, does not make the Qur'an as a source of law.